Potassium-Ion Battery Electrodes from Potassium Ferricyanide Nanoplatelets: Thin Platelets and Thick Electrodes Unlock High Areal Capacity and Excellent Rate Performance - Nicolosi, Valeria; Coleman, Jonathan; Carey, Tian; Konkena, Bharathi (My University, 2025)
Recent efforts to develop cathode materials for potassium-ion batteries (KIBs) have focused on maximizing specific capacity. However, real applications will require thick electrodes with high areal capacity that can achieve reasonable rate performance, which is a significant challenge. While Prussian blue analogs (PBAs) show promise for fast K-ion storage, they often require bespoke synthe- sis. In this study, potassium ferricyanide (K3 Fe(CN)6 , KFC) is explored as a com- mercially available and cost-effective alternative. Using liquid-phase exfoliation, KFC powder is converted into 2D nanoplatelets, which are combined with single wall carbon nanotubes (SWCNT) to form porous, conductive, and mechanically tough electrodes. This KFC/SWCNT nanocomposite delivers reversible capacities up to 98 mAh g−1 at 20 mA g−1 , with 92% capacity retention after 500 cycles. These composite electrodes can be fabricated with thicknesses and areal mass loadings up to 105 μm and 9.6 mg cm−2 respectively and achieve an areal capacity of 0.65 mAh cm−2 at 20 mA g−1 , the highest reported among PBAs. Despite being limited by solid-state diffusion, the short diffusion paths associate with the nanoplatelet geometry enable excellent rate performance
PUBLISHED
Cited by: 0; All Open Access, Hybrid Gold Open Access
Keywords: potassium-ion batteries (KIBs); nanoplatelet geometry; high areal capacity; potassium-ion batteries (KIBs); nanoplatelet geometry; high areal capacity